2010
DOI: 10.1007/s11595-010-0070-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sub-microstructure in concrete with low water-binder ratio by SEM-BSE image analysis

Abstract: The coarse pore system, interfacial transition zone (ITZ) between aggregate and paste matrix and volume fraction of unhydrated cement in concrete (w/c=0.3) containing mineral admixtures were quantitatively characterized by the scanning electron microscope-backscattered electron (SEM-BSE) image analysis technique. The experimental results show that compound addition of slag and fly ash decreases the coarse porosity from 10.17% to 3.74% and the threshold diameter of coarse pore size from 345 µm to 105 µm compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Also, increasing the W/B from 0.40 to 0.50 causes a looser and more porous structure. Thus, this situation enhances the porosity 48 . Besides, the overall trend of the P variation in the mixtures with W/B = 0.5 was similar to W/B = 0.4.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Also, increasing the W/B from 0.40 to 0.50 causes a looser and more porous structure. Thus, this situation enhances the porosity 48 . Besides, the overall trend of the P variation in the mixtures with W/B = 0.5 was similar to W/B = 0.4.…”
Section: Resultsmentioning
confidence: 62%
“…Thus, this situation enhances the porosity. 48 Besides, the overall trend of the P variation in the mixtures with W/B = 0.5 was similar to W/B = 0.4. However, the P content in W/B = 0.5 was higher than in W/B = 0.4.…”
Section: Porosity (P)mentioning
confidence: 67%
“…As for the ITZ thickness, available experimental results do not achieve a consistent conclusion. Qian et al [36] indicated that addition of fly ash decreases the ITZ thickness by 37%. However, other studies showed that the effect of fly ash on the ITZ thickness is insignificant [30,37,38].…”
Section: Experimental Verification and Discussionmentioning
confidence: 99%
“…Meso J.C. [7] had observed ITZ micro structure changes with age after the completion of concrete. The typical thickness of the transition zone between aggregate and cement matrix was approximately 50µm [8] and ITZ was featured by high porosity, large amount of oriented-aligned Ca(OH) 2 accumulation near coarse aggregate surfaces and the presence of micro cracks [1] .…”
Section: Introductionmentioning
confidence: 99%